Evaluation of intraocular lens position during phacoemulsification using intraoperative spectral‐domain optical coherence tomography. Issue 5 (May 2016) - Lytvynchuk, Lyubomyr M.; Glittenberg, Carl G.; Falkner‐Radler, Christiane I.; Neumaier‐Ammerer, Beatrix; Smretschnig, Eva; Hagen, Stefan; Ansari‐Shahrezaei, Siamak; Binder, Susanne
Abstract : Purpose : To assess the position of intraocular lenses (IOLs) at the end of standard phacoemulsification with intraoperative spectral‐domain optical coherence tomography (SD‐OCT). Settings : Department of Ophthalmology, Rudolf Foundation Hospital, Vienna, Austria. Design : Prospective case series. Methods : Standard phacoemulsification with IOL implantation was performed. The Rescan 700 SD‐OCT system was used for intraoperative imaging. The anterior segment of the eye was scanned using SD‐OCT at the end of the surgery. The distance from the IOL optic center and the IOL optic edge to the posterior capsule was measured postoperatively using graphic software. Results : The study comprised 74 patients (101 eyes). The mean axial length was 23.97 mm (range 21.43 to 28.61 mm). The mean IOL power was 20.39 diopters (D) (range 6.5 to 27.5 D). Contact between the IOL and posterior capsule was absent in 88 cases (87.13%), and partial or full contact was present in 13 cases (12.87%). The mean distance between the IOL central optic and posterior capsule was 0.71 pixel (range 0.06 to 1.38 pixels) in 99 cases (98.02%). In 42 cases (57.53%), partial contact between the IOL edges and the posterior capsule was noticed. The mean distance between the IOL edge and posterior capsule was 0.21 pixel (range 0.04 to 0.92 pixel). Conclusions : Intraoperative SD‐OCT facilitated the imaging of IOL position during standard phacoemulsification. Contact between the IOL central optic and posterior capsule at the end of the surgery occurred rarely. Improved IOL design should be considered. Financial Disclosure : Drs. Binder and Glittenberg are consultants to Carl Zeiss Meditech AG. None of the other authors has a financial or proprietary interest in any material or method mentioned.